Peningkatan Kualitas dan Kuantitas Biji Kakao Melalui Intensifikasi Perawatan Kakao, Introduksi Alat Budidaya, dan Pengering Sistem Hybrid - Mercy Bientri Yunindanova; Dimas Rahadian Aji Muhammad; Sigit Prabawa (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2021)
Putat village, Patuk district, Gunung Kidul regency is one of cocoa production center in Yogjakarta. Cocoa bean products in this region have been marketed not only in Yogjakarta but also several areas in Indonesia. In order to support production continuity of cocoa bean productions, to date the farmers face obtacles in cacao plantation maintenance and cocoa beans drying. Thus, this activity aimed to increase quality and quantity of cocoa beans through maintenance intensifications of cacao and introduction of cacao cultivation equipments and cocoa beans drying hybrid system. Partner in this activities were Kelompok Tani Kakao Sido Dadi and cocoa dan chocolate production industry “Joglo Coklat” located in Patuk, Gunung Kidul, Yogjakarta. The activities were conducted in several stages including 1) basic data collection, 2) socialization of cacao plantation maintenance, 3) socialization of cocoa beans drying, 4) introduction of cultivation equipments, 5) contruction of drying chamber, 6) handover of equipment, and 7) evaluation of parnter response. The results of the activity indicated that the provision of information and the introduction of equipment for cacao plant maintenance activities had a positive impact on partners. From the questionnaires, the partners stated the benefits of this activity and the desire for sustainable activities. The introduction of maintenance equipment and cocoa beans drying made it easier for farmers to carry out cultivation, harvest and post-harvest activities of cocoa beans so would be able to improve the quality and quantity of cocoa beans.